ANALISIS KUALITAS AIR IRIGASI AREAL PERSAWAHAN DI DESA RANOYAPO KECAMATAN RANOIAPO KABUPATEN MINAHASA SELATAN - Eucharisty S. Rewur; J.V Bobby Polii; Selvie Tumbelaka (Universitas Sam Ratulangi, 2019)
ABSTRACT The purpose of this study was to determine the water quality in Ranoyapo Village, Ranoiapo District, South Minahasa Regency, which is used as irrigation water in the rice fields at Ranoyapo Village. This study was conducted for three months (3), from September to November 2018, the location of water sampling was at the part before entering the rice field and at the exit area at Ranoyapo Village, then has analyzed at the Manado Industrial Research and Standardization Laboratory Laboratory. The results of the analysis showed that the pH concentration before entering the expanse (6.71), on the exit part of the expanse (6.52) was in the good category. The concentration of DHL before entering the overlay (0.17830 ds / m) at the exit of the overlay (0.15880 ds / m) is in the good category. TDS concentrations before entering the overlay (244 mg / l), at the exit of the overlay (282 mg / l) in the good category. NO3-N concentration before entering the stretch (0.44 mg / l), at the exit of the stretch (089 mg / l) in the good category. The concentration of Clorida before entering the stretch (0,2178 me / l), at the exit of the stretch (0,2178 me / l) is in the good category. The concentration of Boron before entering the stretch (<0.08 mg / l), at the exit of the stretch (<0.08 mg / l) is in the good category. The concentration of PO4-P before entering the overlay (0.03 mg / l), at the exit of the overlay (0.09 mg / l) is in the good category. Potassium concentration before entering the stretch (3.49 mg / l), at the exit of the stretch (3.59 mg / l) is in the bad category. The results of the analysis of irrigation water quality in Ranoyapo Village with the parameters of pH, DHL, TDS, NO3-N, Clorida, Boron, PO4-P in good quality while Potassium in poor quality according to the comparison of Ayers and Wetscot irrigation water quality standards, 1985. Keywords: water quality, irrigation